PYOMETRA WITH UNILATERAL HORN EVACUATION IN A SPITZ BITCH - RAJA, S; SATHESH KUMAR, S; VIJAYARAJAN, A; PRABAHARAN, V; PUSHKIN RAJ, H; VIJAYA KUMAR, M; JAYAGANTHAN, P (The Indian Journal of Animal Reproduction, 2017)
A four and half year old Spitz bitch was presented with vulval discharge, diagnosed for pyometra and therapeutically treated for seven days. The treatment resulted in evacuation of pus from unilateral horn. The animal was further recommended for ovariohysterectomy and had an uneventful recovery.